(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Imaging techniques have been upgraded due to the invention of digital radiography. This advancement has made a massive change in the development of diagnostic procedures. This technique has displaced conventional radiography with digital methods of radiography. This radiography technique was accepted in all kinds of radiography, excluding mammography. There are many assets of using a digital process for imaging, like good quality of image with less dose. It gave accurate diagnosis for assured quality of image with high resolution and to avoid overdose proper guidelines are needed. The technician should be well trained and have adequate knowledge of the appropriate use of digital radiography. The flat detector system depicts a more efficient way to form an image of high quality with a low dose; the quality of the image increases due to the storage phosphor. Many institutions have accepted this digital radiography as it has proven beneficial for diagnostic procedures. Digital radiography has a flat panel detector that results in a high-resolution image. It has been noticed that screen-film radiography has been superseded by Digital radiography. Nowadays, manufacturers have made many improvements derived from the detector and different technology to Digital radiography equipment. Due to digital imaging techniques, x-rays are allowed to store digitally that can use anytime by adjusting contrast according to the interest of vision. This technology has given assurity of not losing any radiograph and allows dispensing throughout hospitals digital by online technology derived from the web. There are so many assets of using digital radiography as it increases patient count. The vigorous high scale of the digital detector with as low as possible radiation dose for the proper usage of this technology, radiologists and radiographers should have adequate knowledge of various technical postulates & image calibre. They should know how to tackle the problem of overexposure or radiation dose.